The soft tissue and skeletal anatomy of two Late Jurassic ichthyosaur specimens from the Solnhofen archipelago - Delsett,Lene L.; Friis,Henrik; Kölbl-Ebert,Martina; Hurum,Jørn H. (PeerJ, 2022)
Ichthyosaurs from the Solnhofen Lagerstätte are among the only examples of soft tissue preservation in the major Middle Jurassic–middle Cretaceous family Ophthalmosauridae. However, few such specimens are currently described, and the taphonomical pathways for the preservation of soft tissue are not well understood. In order to answer this, two new ichthyosaur specimens, one nearly complete and one isolated tail, are described here. The nearly complete specimen is assigned to Aegirosaurus sp. It is accompanied by large amounts of incrustation pseudomorphs (epimorphs) of soft tissue preserved as apatite. It also preserves a nearly complete gastral basket, for the first time in ophthalmosaurids. Soft tissue samples were analyzed using X-ray diffraction (XRD) and scanning electron microscopy (SEM) coupled with energy dispersive spectroscopy (EDS) analysis. The analyses confirm the presence of apatite, with phosphate most likely derived from the body itself.
Keywords: Ichthyosaur; Solnhofen; Taphonomy; Soft tissue; Aegirosaurus; Phosphatization; Ophthalmosauridae